Presentation. Borders, Races, Gender and Labor in Kantian Philosophy - Renato Jesús, Paulo; Herrero Olivera, Laura (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The eight papers in the Special Dossier for the Tricentenary of Immanuel Kant’s Birth (1724-1804) ‘Borders, Races, Gender and Labor in Kantian Philosophy’ reflect upon these issues and their presence in the Kantian legacy from a contemporary point of view. Other concepts and themes emerge as transversal threads linking these contributions such as the feeling of respect, duties, rights, and the role that communities play or the ethical-juridical function of the social contract. Other philosophers and philosophical traditions take part in the discussions, such as Rousseau, Fichte, Hegel, Derrida, Foucault, Hannah Arendt or Susan Moller Okin. The result is a wide perspective that invites us to go back to Kantian texts.